(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
The paper provides an analysis of the so-called Sabellian inscription of Velletri. It focuses on the norms established in this text for the expiatory sacrifice that it prescribes. These norms use precise ritual categories and select precise values for the corresponding variables, which are definitory for the sacrifice. The use of such well-defined technical terms accounts for the brevity of the text and is compatible with its being probably designed for a readership of priests.